Studies in the seed ecology and seedling Phenology of Andrographis paniculata (Brum. f.) Wall. ex Ness in West Bengal, India - Kundu, Arijit; Bisui, Sourabh; Layek, Ujjwal; Karmakar, Prakash (Plant Science Today, 2024)
Andrographis paniculata (Brum. f.) Wall. ex Nees is an important medicinal plant of tropical Asia and has been used widely for a long time for different clinical ailments. Despite profuse flowering and a high percentage of fruit set,the number of seedlings in the natural population is the bare minimum. Knowledge regarding the seed ecology and seedling phenology of A. paniculata, is needed to formulate conservation strategies for the species. Therefore, a detailed study on seed ecology and seedling phenology has been conducted. During seed ecological studies,seed production, seed-set percentage, seed-ovule ratio, mechanism of seed dispersal, seed structure along with germination status, viability, dormancy and its breaking, and percentage of moisture content loss have been studied. Seeds exhibit some kind of dormancy [germination percentage (GP) = 28.51 ± 0.98, mean germination time (MGT) = 33.07± 0.89 days, and germination index (GI) = 0.73 ± 0.08] which can be effectively overcome through acid scarification using H2SO4 and hot water treatment. The species shows epigealphanerocotylar germination. The hypocotyls exhibit rapid growth, and cotyledons emerged at 7.52±0.27 TARA (Time After Radicle Appearance in days). Seedling is characterised by a thickened, hairy hypocotyl, a distinct collet, a pair of paracotyledons, and three pairs of eophylls in opposite decussate phyllotaxy. The studies on seed ecology and seedling phenology play a significant role in understanding how the shortening of the inception period enhances the germination status, and distinct seedling morphology provides the opportunity to formulate conservation strategies in their wild habitat.